The role of legislation and laws in supporting and developing the tourism industry Analytical study on one of the challenges of the investment process for the tourism sector in Iraq - Esraa Saad Fahad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The world is witnessing large, rapid and continuous developments in the tourism industry, which represents an integrated system of relations and tourism activities that overlap and complement each other due to its importance and influence in supporting the economies of countries as it is a civilized industry that does not pollute the environment and supports and generates national income. The tourism sector in Iraq, which is the legislation, especially with regard to tourism investments, starting with that to shed light at first on clarifying the concept of tourism and its importance as a national development strategy, and then reviewing the Iraqi laws on the tourism sector with a reading of the contents of the Iraqi investment law. The research reached a set of conclusions and recommendations, the most prominent of which is the need to issue legislation supportive of the advancement of the tourism sector in Iraq, starting with the activation of investment in all its activities that attract local and foreign investments and organize tourism work, because Iraq has a diversity of tourism destinations represented by geographical, natural, cultural and heritage Cultural and sacred religious sites, to have an active role in achieving sustainable and stable development that starts and is centered around a basic pillar of advancing this sector as an industry that supports the national economy.